2006
DOI: 10.1086/500175
|View full text |Cite
|
Sign up to set email alerts
|

On the Lengths, Colors, and Ages of 18 Face‐on Bars

Abstract: Along with a brief analysis we present data obtained from BVRI and Ks images of a sample of 19 galaxies (18 barred and 1 unbarred) which will be further explored in a future paper. We measured the lengths and colors of the bars, created color maps and estimated global color gradients. Applying a method developed in a companion paper, we could distinguish for 7 galaxies in our sample those whose bars have been recently formed from the ones with already evolved bars. We estimated an average difference in the opt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 39 publications
9
42
0
Order By: Relevance
“…Shen & Sellwood 2004;Villa-Vargas et al 2010;Athanassoula et al 2013). This is supported by studies showing that bars are typically composed of old stars (Gadotti & de Souza 2006;Sánchez-Blázquez et al 2011).…”
Section: Introductionmentioning
confidence: 59%
“…Shen & Sellwood 2004;Villa-Vargas et al 2010;Athanassoula et al 2013). This is supported by studies showing that bars are typically composed of old stars (Gadotti & de Souza 2006;Sánchez-Blázquez et al 2011).…”
Section: Introductionmentioning
confidence: 59%
“…Bars are typically dominated by evolved stellar populations (Gadotti & de Souza 2006), although they are also associated with enhanced nuclear and circumnuclear star formation (Ho, Filippenko & Sargent 1997), and frequently exhibit dust lanes, which is a signature of radially inflowing gas (Kormendy 1982;Athanassoula 1992;Sellwood & Wilkinson 1993;Friedli & Benz 1993). Barred galaxies are also observed to have larger reservoirs of molecular gas in their centers relative to unbarred galaxies (Sakamoto et al 1999;Sheth et al 2005) and flatter chemical abundance gradients (Zaritsky, Kennicutt & Huchra 1994;Martin & Roy 1994).…”
Section: Bulges Pseudobulges and Barsmentioning
confidence: 99%
“…In general, star formation is located in the circumnuclear regions and in the ends of bars, while bars are typically dominated by evolved stellar populations (Gadotti & de Souza 2006). In a study of the barred spiral NGC 5383, Sheth et al (2000) found weak Hα emission in the bar between the bar ends and the central region despite the high gas column density in the bar dust lanes.…”
Section: Bar-driven Star Formation and Galactic Evolutionmentioning
confidence: 99%